What's cooking in the androgynous kitchen: gender & performance in Anna Gavalda's Ensemble c'est tout - Heraud, Abby R. (Kansas State University, 2009)
According to Feminist Theory, the social construction of gender is carried out through ritualistic or performative acts in everyday life. The idea of “doing” gender, or the “understanding of gender as a routine accomplishment embedded in everyday interaction” has been commonplace in this field for over three decades (West and Zimmerman 125). Contemporary French author Anna Gavalda toys with typical gender stereotypes in her novel Ensemble c'est tout creating characters who “do” gender and culture utilizing a mix of stereotypical and subversive gender traits. In this thesis I will discuss and analyze how Gavalda's main characters simultaneously accept and reject many gender stereotypes, displaying a variety of masculine and feminine traits in their daily lives, performing their genders in an unconventional fashion, and promoting an ideal of androgynous behavior. In the end, Gavalda manages to create a sort of “spatial justice” in which the characters fulfill more than just the traditional roles society expects from them. The majority of Gavalda's work integrates French culture, specifically the French meal, in order to set the tone. True to form, she highlights the importance of commensality in French society with considerable amounts of the story's intrigue taking place around meals. The meals themselves become performative acts, ritualized and carried out in much the same way as gender. Gavalda promotes the institution of the French “repas” and the conviviality that accompanies it. Her representations of food and gender beg a variety of questions relating to the role of the modern French woman's appetite and femininity, hierarchies in (and out) of the kitchen, as well as the notion of class in relation to eating well. By combining typical gender expectations with more subtle subversion of societal roles, is Gavalda in fact cooking up a recipe for an androgynous kitchen? The integration of these gender behaviors built around the institution of the French “repas” underscores a shift in the current societal standards promoting a new collective ideal for social change.
Keywords: Anna Gavalda; feminism; Literature, Modern (0298)